Formative research to develop diabetes self-management education and support (DSMES) program for adults with Type 1 Diabetes. Issue 4 (July 2021) - Gupta, Lovely; Lal, Priti Rishi; Gupta, Yashdeep; Goyal, Alpesh; Khanna, Aparna; Tandon, Nikhil
Abstract: Background and aim: There is a lack of data on effectiveness of diabetes self-management education and support (DSMES) programs for South Asian adults with type 1 diabetes mellitus (T1DM). This formative research was conducted to explore existing practices on the said subject and gather information for planning an intervention program. Methods and materials: We conducted in-depth semi-structured interviews with endocrinologists, dieticians, diabetes educators and adults with T1DM. The participants were selected from a mix of public and private health facilities. Thematic analysis using inductive and deductive approach was undertaken. The intervention was developed and refined using the principles of FUSED and COM-B models. Results: In total, 28 in-depth interviews were conducted, 18 with health care professionals and 10 with adult individuals with T1DM. The results demonstrated deficiencies in the implementation of a structured self-management program for diabetes owing to several patient and healthcare system-related factors. A detailed nutritional counseling was provided at all sites by a qualified dietitian, however, carbohydrate counting was not routinely practiced. The interviews of this formative research revolved around: (a) evaluation of the existing usual care and gaps in implementation of a structured DSMES program, and (b) development of themes that will help in formulation of an intervention package and its effective delivery to the participants. Conclusion: This research study comprehensively investigated the existing practices among diabetes-health care professionals caring for persons living with T1DM and rendered insights towards development of a scientific DSMES program. Highlights: Diabetes management (nutrition) practices at hospitals were investigated. Deficiencies in implementation of carbohydrate counting education were found. Opportunities for development of an education intervention program were explored.